RNA Binding by the Campylobacter jejuni Post-transcriptional Regulator CsrA - El Abbar, Faiha M.; Li, Jiaqi; Owen, Harry C.; Daugherty, C. Luke; Fulmer, Claudia A.; Bogacz, Marek; Thompson, Stuart A. (Frontiers in Microbiology, 2019)
Campylobacter jejuni is a Gram-negative rod-shaped bacterium that commensally inhabits the intestinal tracts of livestock and birds, and which also persists in surface waters. C. jejuni is a leading cause of foodborne gastroenteritis, and these infections are sometimes associated with the development of post-infection sequelae such as Guillain-Barré Syndrome. Flagella are considered a primary virulence factor in C. jejuni, as these organelles are required for pathogenicity-related phenotypes including motility, biofilm formation, host cell interactions, and host colonization. The post-transcriptional regulator CsrA regulates the expression of the major flagellin FlaA by binding to flaA mRNA and repressing its translation. Additionally, CsrA has previously been shown to regulate 120-150 proteins involved in diverse cellular processes. The amino acid sequence of C. jejuni CsrA is significantly different from that of Escherichia coli CsrA, and no previous research has defined the amino acids of C. jejuni CsrA that are critical for RNA binding. In this study, we used in vitro SELEX to identify the consensus RNA sequence mAwGGAs to which C. jejuni CsrA binds with high affinity. We performed saturating site-directed mutagenesis on C. jejuni CsrA and assessed the regulatory activity of these mutant proteins, using a reporter system encoding the 5’ untranslated region (5’UTR) upstream of flaA linked translationally to the C. jejuni astA gene. These assays allowed us to identify 19 amino acids that were involved in RNA binding by CsrA, with many but not all of these amino acids clustered in predicted beta strands that are involved in RNA binding by E. coli CsrA. Decreased flaA mRNA binding by mutant CsrA proteins L2A and A36V was confirmed by electrophoretic mobility shift assays. The majority of the amino acids implicated in RNA binding were conserved among diverse Campylobacter species.